Hunting Technology and Prepared Landscapes in the South-Central Andes. (1st October 2016) - Moreno, Enrique Alejandro
Abstract : Camelid hunting has been a central practice for the social reproduction of human populations who occupied the south-central Andes through time. Among the evidence that contributes relevant information about this subject matter are projectile points and their connection with different weapon systems and the hunting strategies implemented by these groups. In this work, we will present information obtained from an intensive survey realized in two archaeological places of the Catamarca highlands. The projectile points recovered in the fieldwork were analyzed in order to understand the manufacturing techniques and the assignment to different types of weapon and to different historical time periods. Finally, with this information, we will evaluate the different hunting strategies performed by hunters and compare this model with other proposals made in other studies in the same landscape.